2019
DOI: 10.1101/633156
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Kinetic characteristics of propofol-induced inhibition of electron-transfer chain and fatty acid oxidation in human and rodent skeletal and cardiac muscles

Abstract: Introduction: Propofol causes a profound inhibition of fatty acid oxidation (FAO) and reduces spare electron transfer chain (ETC) capacity in a range of human and rodent cells and tissues -a feature that might be related to the pathogenesis of Propofol Infusion Syndrome. We aimed to explore the mechanism of propofol-induced alteration of bioenergetic pathways by describing its kinetic characteristics.Methods: We obtained samples of skeletal and cardiac muscle from Wistar rat (n=3) and human subjects: vastus la… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…The unsaturated fatty acids decreased and saturated fatty acids increased, and were relatively unaffected by addition of propofol (1.75 to 17.5 μgl −1 ) in in vitro analysis (Appendix B, http://links.lww.com/EJA/A604). Previous in vitro studies on human skeletal and heart muscle cell bioenergetics have shown a profound inhibitory effect of propofol on fatty acid oxidation (FAO) 37,38 . On the basis of previous research, after an overnight fast, FAO may account for up to 70% of total body energy expenditure 39 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The unsaturated fatty acids decreased and saturated fatty acids increased, and were relatively unaffected by addition of propofol (1.75 to 17.5 μgl −1 ) in in vitro analysis (Appendix B, http://links.lww.com/EJA/A604). Previous in vitro studies on human skeletal and heart muscle cell bioenergetics have shown a profound inhibitory effect of propofol on fatty acid oxidation (FAO) 37,38 . On the basis of previous research, after an overnight fast, FAO may account for up to 70% of total body energy expenditure 39 .…”
Section: Discussionmentioning
confidence: 99%
“…Previous in vitro studies on human skeletal and heart muscle cell bioenergetics have shown a profound inhibitory effect of propofol on fatty acid oxidation (FAO). 37,38 On the basis of previous research, after an overnight fast, FAO may account for up to 70% of total body energy expenditure. 39 In theory, a disruption of fatty acid utilisation could lead to changes in the circulating lipid profile.…”
Section: Discussionmentioning
confidence: 99%
“…Although the molecular structures of anesthetics are usually different, most can cause changes in multiple functions at the mitochondrial level (3). For example, the occurrence of propofol infusion syndrome (PRIS) is hypothesized to result from direct interference with mitochondrial respiratory chains or hindrance of fatty acid oxidation-related functions (4).…”
Section: Introductionmentioning
confidence: 99%